Sakai Community in the Squeeze of Development: Community Development Program and Social Disintegration - Justicio, Muhammad Deckaryan Lexa; Gunawan, Budhi (Universitas Andalas, 2025)
Community empowerment programs seem to be a necessity, especially when development and industrialization programs have negative impacts on various groups, including indigenous communities. However, community empowerment, which is intended to improve the lives of affected communities, in practice often has unanticipated impacts. This study analyzes the social dynamics of the Sakai community in Riau Province related to the empowerment programs received by the community. This study used a mini-ethnography method by conducting participant observation and non-participatory observation techniques as well as in-depth interviews in data collection. To complete the data, secondary data collection was also carried out, including those that could be obtained online. The results of the study indicate that the empowerment programs that have been carried out, in addition to providing benefits to some members of the community, have also created gaps among community members which have led to the social disintegration of the Sakai community. The implementation of community empowerment programs by companies evenly and the involvement of the government and other stakeholders in program implementation are necessary.